2016
DOI: 10.1108/mf-08-2014-0230
|View full text |Cite
|
Sign up to set email alerts
|

Forecasting time-varying daily betas: a new nonlinear approach

Abstract: Purpose -The purpose of this paper is to examine the predictive ability of different well-known models for capturing time variation in betas against a novel approach where the beta coefficient is treated as a function of market return. Design/methodology/approach -Different GARCH models, the Kalman filter algorithm and the Schwert and Seguin model are used against our novel approach. The mean square error, the mean absolute error and the Diebold and Mariano test statistic constitute the measures of forecast ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 59 publications
0
3
0
Order By: Relevance
“…The exponential constant term could be thought of being a constant beta coefficient when the remaining terms are zero. Messis and Zapranis (2016) use these specific coefficients for predicting stock betas and compare their accuracy prediction with other well‐known models. The results indicate that the new approach overwhelms the other models in longer samples.…”
Section: Methodological Frameworkmentioning
confidence: 99%
“…The exponential constant term could be thought of being a constant beta coefficient when the remaining terms are zero. Messis and Zapranis (2016) use these specific coefficients for predicting stock betas and compare their accuracy prediction with other well‐known models. The results indicate that the new approach overwhelms the other models in longer samples.…”
Section: Methodological Frameworkmentioning
confidence: 99%
“…This study uses the two step procedure for finding the effect of regulation on systemic risk. The two steps are: The first step was to estimate systemic risk ( β ) using Kalman filter along with CAPM (Barcelos and da Silveira Bueno, 2010; Chalmeau, 2012; Messis and Zapranis, 2016). The β values were not expected to be constant due to the regulatory and policy announcements during the study period, which is confirmed by applying the stationarity tests. The second step was the use of event study methodology for finding the effect of regulatory announcements on daily β (Binder, 1985; Chalmeau, 2012).…”
Section: Methodsmentioning
confidence: 99%
“…The first step was to estimate systemic risk ( β ) using Kalman filter along with CAPM (Barcelos and da Silveira Bueno, 2010; Chalmeau, 2012; Messis and Zapranis, 2016). The β values were not expected to be constant due to the regulatory and policy announcements during the study period, which is confirmed by applying the stationarity tests.…”
Section: Methodsmentioning
confidence: 99%